Lifileucel, a Tumor-Infiltrating Lymphocyte Therapy, in Metastatic Melanoma. Issue 24 (20th August 2021) - Sarnaik, Amod A.; Hamid, Omid; Khushalani, Nikhil I.; Lewis, Karl D.; Medina, Theresa; Kluger, Harriet M.; Thomas, Sajeve S.; Domingo-Musibay, Evidio; Pavlick, Anna C.; Whitman, Eric D.; Martin-Algarra, Salvador; Corrie, Pippa; et al.
Abstract : PURPOSE: Effective treatment options are limited for patients with advanced (metastatic or unresectable) melanoma who progress after immune checkpoint inhibitors and targeted therapies. Adoptive cell therapy using tumor-infiltrating lymphocytes has demonstrated efficacy in advanced melanoma. Lifileucel is an autologous, centrally manufactured tumor-infiltrating lymphocyte product. METHODS: We conducted a phase II open-label, single-arm, multicenter study in patients with advanced melanoma who had been previously treated with checkpoint inhibitor(s) and BRAF ± MEK targeted agents. Lifileucel was produced from harvested tumor specimens in central Good Manufacturing Practice facilities using a streamlined 22-day process. Patients received a nonmyeloablative lymphodepletion regimen, a single infusion of lifileucel, and up to six doses of high-dose interleukin-2. The primary end point was investigator-assessed objective response rate (ORR) per RECIST, version 1.1. RESULTS: Sixty-six patients received a mean of 3.3 prior therapies (anti–programmed death 1 [PD-1] or programmed death ligand 1 [PD-L1]: 100%; anticytotoxic T-lymphocyte-associated protein-4: 80%; BRAF ± MEK inhibitor: 23%). The ORR was 36% (95% CI, 25 to 49), with two complete responses and 22 partial responses. Disease control rate was 80% (95% CI, 69 to 89). Median duration of response was not reached after 18.7-month median study follow-up (range, 0.2-34.1 months). In the primary refractory to anti–PD-1 or PD-L1 therapy subset, the ORR and disease control rate were 41% (95% CI, 26 to 57) and 81% (95% CI, 66 to 91), respectively. Safety profile was consistent with known adverse events associated with nonmyeloablative lymphodepletion and interleukin-2. CONCLUSION: Lifileucel demonstrated durable responses and addresses a major unmet need in patients with metastatic melanoma with limited treatment options after approved therapy, including the primary refractory to anti–PD-1 or PD-L1 therapy subset.